Biomass ashes to produce an alternative alkaline activator for alkali-activated cements - Soriano, L. (2022)
In the last decade, herbaceous and agricultural biomass have been used as an alternative energy source. As consequence, large amounts of residual ashes containing potassium (potassium-rich ashes) have been generated. Olive biomass ash (OBA) and almond shell ash (ABA) have been successfully used as alkali source in the alkaline activation of ground granulated blast furnace slag (BFS). This study focuses on the production of new and alternative alkaline activators for BFS systems using nutshell ashes (NBA), mango seed-bark ashes (MBA) and hazelnut shell ashes (HBA). The chemical and mineralogical composition of these ashes were assessed and, the mechanical and microstructural properties of BFS pastes activated with NBA, MBA and HBA were evaluated. The results indicated that all assessed materials are potassium-rich ashes differing mainly on the amount of CaO and P2O5. The compressive strength of BFS pastes yielded about 26 MPa and, according to FESEM/EDS analysis, K2O (in the range 8.03–24.33%) replaces chemical bounded Ca+2, forming C-(K)-A-S-H gel.